Świadek męczeństwa i jego rola w świetle jurysprudencji Kongregacji Spraw Kanonizacyjnych - Zdzisław J. Kijas (Polonia Sacra)
In the legal understanding, martyrdom requires external recognition as well as external evaluation. For this reason, the visual witness appears in the context of death (the witness of martyrdom). His job is to cognitively and consciously evaluate the fact of the physical loss of life. The reason to begin the process of canonization can only come about in close connection with the evaluation of internal state of love and faith of the martyred person; but not necessarily. Since death for the faith has the value of the Sacrament of Baptism, it may happen that an unbeliever or someone not practicing his faith, can give his life for the faith. Through this act, he absolves his unbelief or committed sins and can become blessed or a saint of the church. This is, however, a unique gift of God’s grace which is rather rare. Usually a zealous, faith-filled life, prepares the believer to follow the footprints of his Master and give his own life.